Cardiotoxicity with doxorubicin, trastuzumab, and development of the metabolic syndrome: Case report (Research, Society and Development, 2021)
The aim of this report is to present a case of a breast cancer patient who showed a reduction in the left ventricular ejection fraction and developed the metabolic syndrome after doxorubicin and trastuzumab use. It was analyzed if those drugs may be related to cardiotoxicity or be a possible cause for metabolic syndrome. With increased cancer survival, many patients may still develop metabolic syndrome, which has a multifactorial nature A 46-year-old female patient with infiltrated breast cancer exhibiting reduced left ventricular ejection fraction after chemotherapy neoadjuvant with doxorubicin and then with isolated trastuzumab. Chemotherapy was discontinued, and it was prescribed tamoxifen. The patient was referred to the cardiologist and nutritionist for a follow-up of the metabolic syndrome. Importance of early identification and monitoring of cardiotoxicity, avoiding the cardiovascular complications of cancer treatment and the preventing interruption of therapy.